Electrochemical properties of carbon-wrapped FeF3 nanocomposite as cathode material for lithium ion battery. (10th August 2018) - Li, Jia; Fu, Licai; Xu, Zhanwei; Zhu, Jiajun; Yang, Wulin; Li, Deyi; Zhou, Lingping
Abstract: Iron fluorides have drawn much attention in Li-ion batteries due to high theoretical capacity. However, its application progress is hampered by the inferior electrode cyclability and rate capability. The main issue in this work is to find effective ways to improve the electrochemical activity of iron fluoride (FeF3 ), and enhance the electrochemical properties. Herein, carbon wrapped FeF3 nanocomposite has been synthesized progressively by carbon coating and fluorination. This structure not only keeps the grain size of FeF3 about 60 nm, but also immerses the electrode in the electrolyte fully. So the electrode shows excellent electrochemical activity. This nano-composite exhibits an initial discharge capacity of ∼166.4 mAh g −1 in the voltage of 2.0–4.5 V at 20 mA g −1 . After 100 cycle, the discharge capacity keeps about 126.3 mAh g −1, with the fading rate of ∼0.24%. Furthermore, the EIS of carbon winded FeF3 indicates that the transmission ability of lithium ion improved greatly. This structure is very meaningful to provide a synthetic approach to prepare the cathode material. Graphical abstract: Image 1 Highlights: FeF3 /C composite with high surface area is prepared by simple processes. The mechanism and formation of carbon wrapping are revealed. FeF3 /C nano composite exhibited an initial capacity of 162.1 mAh g −1 . FeF3 /C shows good cycling performance and high discharge efficiency.